2004
DOI: 10.1088/0022-3727/37/17/019
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of O2(a 1 g) production by a non-self-sustained discharge for oxygen–iodine laser pumping

Abstract: O2(a 1Δg) production in a non-self-sustained discharge (ND) in pure oxygen and oxygen mixtures with inert gases (Ar and He) has been studied. A self-consistent model of ND in pure oxygen is developed, allowing us to simulate all the obtained experimental data. Agreement between the experimental and simulated results for pure oxygen over a wide range of reduced electric fields was reached only after taking into account the ion component of the discharge current. It is shown that the correct estimation of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 26 publications
3
99
0
Order By: Relevance
“…In addition to the expected emission from I*, bright visible fluorescence from the I B-X transition was also present. The latter was not seen for the same flow conditions without the wall coating due to the rapid removal of I by O atom reactions (14) and (15). Detection of the B-X emission implies that the wall-catalyzed production of O (a) consumes O atoms, but the mechanism of this reaction is not yet known.…”
Section: Kinetics Issuesmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition to the expected emission from I*, bright visible fluorescence from the I B-X transition was also present. The latter was not seen for the same flow conditions without the wall coating due to the rapid removal of I by O atom reactions (14) and (15). Detection of the B-X emission implies that the wall-catalyzed production of O (a) consumes O atoms, but the mechanism of this reaction is not yet known.…”
Section: Kinetics Issuesmentioning
confidence: 96%
“…Extensive modeling of O discharges has been used to explore the optimum conditions for producing high yields and high concentrations of O (a) [3,[12][13][14][15][16][17]. One of the limitations imposed by the discharge environment is that O (a) is both generated and destroyed by electron impact processes.…”
Section: Basic Principles Of Discharge Oxygen-iodine Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…O 2 (b 1 Σ + g ) molecules. Recent theoretical and experimental studies of physical and chemical processes in oxygen plasma generated by a non-self-sustained discharge [10][11][12][13][14][15] showed that significant amounts of singlet oxygen O 2 (a 1 Δ g ) and O 2 (b 1 Σ + g ) molecules (≈4%) can be obtained even at pressures close to the atmospheric value. In contrast to excitation of O 2 molecules by laser radiation, the plasma in the electric discharge always contains small amounts of atomic oxygen (O) and ozone molecules (O 3 ), as well as vibrationally excited O 2 molecules in the ground electronic state [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%